2017
DOI: 10.1016/j.jsat.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Examining the reach of a brief alcohol intervention service in routine practice at a level 1 trauma center

Abstract: The American College of Surgeons requires Level I and II trauma centers to provide brief intervention services to traumatically injured patients who screen positive for alcohol. Despite evidence supporting substantial cost savings and reduced re-injury associated with these services, brief interventions may not be uniformly delivered owing to a variety of demographic, clinical and operational characteristics. To inform service adjustments that may improve the reach of such services, we compared trauma patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…As such, one may assume that willing and unwilling employees were not systematically different with regard to how much they drank, how they construed drinking in general as well as work-related drinking more specifically, and what effects they expected alcohol to produce. These findings are in line with previous studies that have revealed no systematic differences in terms of intervention participation based on weekly consumption and frequency of heavy episodic drinking (35), overall alcohol use and consequences (36), typical number of drinks per week (38), or blood alcohol concentration (37). We did, however, find that those willing to participate reported less alcohol-related presenteeism, i.e., occurrences of episodes where on-the-job performance have been thwarted by alcohol consumption.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As such, one may assume that willing and unwilling employees were not systematically different with regard to how much they drank, how they construed drinking in general as well as work-related drinking more specifically, and what effects they expected alcohol to produce. These findings are in line with previous studies that have revealed no systematic differences in terms of intervention participation based on weekly consumption and frequency of heavy episodic drinking (35), overall alcohol use and consequences (36), typical number of drinks per week (38), or blood alcohol concentration (37). We did, however, find that those willing to participate reported less alcohol-related presenteeism, i.e., occurrences of episodes where on-the-job performance have been thwarted by alcohol consumption.…”
Section: Discussionsupporting
confidence: 92%
“…In line with the Swedish study, participants and non-participants in the German study did not differ on variables such as gender, employment status, and alcohol consumption. Similar results have been found among American trauma patients eligible for a brief face-to-face intervention administered by health care personnel (37). A study of a general population sample in Germany (visitors at a municipal registry office, i.e., a public authority for registration, passport and vehicle administration issues) (38) did, however, report that low-risk drinkers had higher odds of participating in a digital intervention with computer-generated feedback than risky drinkers.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Prior studies have shown that shorter hospital lengths of stay, as seen in our study population, are a barrier to intervention and treatment of chronic disease. 8 However, despite median stays ranging from 2 to 4 days, outcomes were significantly different between cohorts. The cohorts that had patients with UD-UD and PD-UD cohorts-had higher rates of inpatient complications, intensive care unit admission, and 30-day ED visits.…”
Section: Discussionmentioning
confidence: 97%
“…For trauma patients diagnosed with substance and alcohol use, some programs have shown outpatient success when screening and interventions are initiated during inpatient trauma admission. 8 Although early screening measures can be cost-effective and do not require additional patient testing or procedures, best-practice models are lacking for young adult inpatients. 9 We hypothesized that there would be a high prevalence of chronic disease, both diagnosed and undiagnosed, in the young adult trauma population.…”
mentioning
confidence: 99%